2018
DOI: 10.1159/000486708
|View full text |Cite
|
Sign up to set email alerts
|

Different Characteristics, Clinical Outcomes, and Left Atrial Reverse Remodeling in Patients with Mitral Stenosis Maintaining Sinus Rhythm for at Least 10 Years after Successful Percutaneous Mitral Valvuloplasty

Abstract: Background: We aimed to investigate the characteristics and echocardiographic changes in patients with severe mitral stenosis (MS) who maintained sinus rhythm (SR) for at least 10 years after successful percutaneous mitral balloon valvuloplasty (PMV). Methods: We retrospectively reviewed 107 patients who had successful PMV and follow-up echocardiography for at least 10 years without mitral valve surgery. Preprocedural, immediate postprocedural (PMV), and long-term follow-up echocardiography (at least 10 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…However, the small number of patients on antiarrhythmic drugs after PMBC denotes that those who cardioverted and restored SR at follow-up were most likely a minority. Despite these limitations, this important paper by Cho et al [11] provides further evidence supporting the detrimental effects of AF after PMBC. Although PMBC does not have an established antiarrhythmic action regarding incident AF despite postinterventional hemodynamic improvement, the results of their study favor an earlier intervention in asymptomatic patients with severe MVS who are at increased risk to develop permanent AF.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…However, the small number of patients on antiarrhythmic drugs after PMBC denotes that those who cardioverted and restored SR at follow-up were most likely a minority. Despite these limitations, this important paper by Cho et al [11] provides further evidence supporting the detrimental effects of AF after PMBC. Although PMBC does not have an established antiarrhythmic action regarding incident AF despite postinterventional hemodynamic improvement, the results of their study favor an earlier intervention in asymptomatic patients with severe MVS who are at increased risk to develop permanent AF.…”
mentioning
confidence: 85%
“…In this issue of Cardiology, Cho et al [11] present the results of a retrospective study of 107 patients with rMVS who underwent successful PMBC and were followed up with echocardiography for at least 10 years. The authors observed that almost half of the patients who underwent PMBC were still on SR at the very long-term follow-up and that the maintenance of the SR correlated with the presence of preprocedural SR and LA diameter < 50 mm.…”
mentioning
confidence: 99%